Nitrite-induced Germination of Putrefactive Anaerobe 3679h Spores - Duncan, Charles L. (1968)
Sodium nitrite alone has been shown to stimulate germination of PA 3679h spores. The process was accelerated by using increased concentrations of sodium nitrite, a low pH, and a high temperature of incubation. At low concentrations of nitrite (0.01 to 0.2%), the delay of 36 to 48 hr occurred before germination commenced at 37 C. However, with 3.45% nitrite at 45 C and pH 6.0, most of the spores germinated within 1 hr. At pH 7.0, the germination rate decreased markedly, and at pH 8.0 it was nil. The greatest acceleration in germination rate occurred near 60 C. Hydroxylamine was completely inhibitory to nitrite-induced germination. Sodium nitrite, in turn, inhibited germination by l-alanine, the degree of inhibition being influenced by nitrite concentration and pH.